Low-density low-thermal-conductivity two-component polyurethane structural adhesive and preparation method thereof

By developing a specific ratio of low-density and low-thermal conduction two-component polyurethane structural adhesive, the problem of difficult to maintain the internal temperature of the battery cell in a low temperature environment is solved, and the density, low thermal conductivity and high bonding strength are achieved. The characteristics of the battery pack structure are met with the safety requirements.

CN119463787APending Publication Date: 2025-02-18HANGZHOU ZHIJIANG SILICONE CHEM +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411594879.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In the field of new energy power batteries, it is difficult to effectively maintain the internal temperature of the battery cell under low temperature environments, resulting in a decrease in ion transmission efficiency and affecting battery performance. Existing solutions such as foamed polyurethane glue and aerogels have problems such as difficult to control the foaming ratio and insufficient strength.

Method used

开发一种低密度低导热双组份聚氨酯结构胶,通过特定配比的A组分和B组分,包括改性蓖麻油、聚醚多元醇、扩链剂、阻燃填料、中空填料等组分,实现产品密度低、导热低、粘接强度高的特性。

Benefits of technology

A structural bonding glue with excellent flame retardant properties has been realized, with a density range of 0.5~1.0g/cm3 and a thermal conductivity of 0.10~0.25W/m·k, which meets low density, low thermal conductivity and bond strength The high demand solves the problems of excessive density and excessive thermal conductivity in the prior art.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005127401650000121
    Figure BDA0005127401650000121
  • Figure BDA0005127401650000131
    Figure BDA0005127401650000131
Patent Text Reader

Abstract

The invention provides a low-density low-thermal-conductivity two-component polyurethane structural adhesive. The low-density low-thermal-conductivity two-component polyurethane structural adhesive consists of a component A and a component B in a volume ratio of (0.8-1.2): 1, the component A comprises 10-40 parts by weight of modified castor oil; 10 to 20 parts by weight of polyether polyol; 1-5 parts by weight of a chain extender; 20-40 parts by weight of a flame-retardant filler; 1-20 parts by weight of a hollow filler; 1-5 parts by weight of white carbon black; 1-5 parts by weight of a molecular sieve; 0.1 to 1 part by weight of a tackifier; 0.1-1 part by weight of yellow color paste; the component B comprises the following components in parts by weight: 30-50 parts of isocyanate; 10 to 30 parts by weight of polyester polyol; 20-40 parts by weight of a flame-retardant filler; 1-20 parts by weight of a hollow filler; 1-5 parts by weight of white carbon black; 1-5 parts by weight of a molecular sieve; 0.1-1 part by weight of an anti-aging agent; 0.1-1 part by weight of a water absorbent; and 0.1-1 part by weight of blue color paste. The low-density low-heat-conductivity two-component polyurethane structural adhesive is low in density, low in heat conductivity, high in bonding strength, non-foaming type and excellent in flame retardant property, and the problems that an existing two-component polyurethane structural adhesive is too high in density and too high in heat conductivity coefficient are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyurethane structural adhesives, and more specifically to a low-density and low-thermal-conductivity two-component polyurethane structural adhesive and a preparation method thereof. Background Art

[0002] At present, in the field of new energy power batteries, low-temperature endurance of batteries is a challenge. The reason is that in extremely cold weather, the outside temperature has a greater impact on the temperature inside the battery pack, which makes the temperature of the battery cell too low, thereby reducing the ion transmission efficiency inside the battery cell and affecting the final battery performance. In order to solve the above technical problems, the method adopted in the prior art is to reduce the thermal conductivity of the structural glue around the battery cell, so that the temperature inside the battery cell can be better maintained in a low-temperature environment. Specifically, it includes the following two solutions: one is to use foaming polyurethane glue. The so-called foaming polyurethane glue refers to the glue that continuously foams during the curing process after the glue is applied to form a hollow structure. The final product has low density and low thermal conductivity; but this solution has two problems. First, the foaming ratio is not easy to control. Because it is a chemical reaction foaming, the foaming ratio has poor repeatability, especially now that the structure of the battery pack is becoming more and more streamlined and the internal space is small. Once the foaming ratio is out of control, the glue will obviously overflow and affect the appearance; secondly, the strength of the foaming type of glue is low and cannot meet the safety requirements of the battery pack structure bonding. The second solution is to use aerogel, which has a fixed foaming ratio and good flame retardancy; however, it is too expensive and has insufficient adhesion to the battery cells and side panels. Summary of the invention

[0003] In view of this, the object of the present invention is to provide a low-density and low-thermal conductivity two-component polyurethane structural adhesive and a preparation method thereof. The product provided by the present invention has low density, low thermal conductivity, high bonding strength, and is a non-foaming structural adhesive with excellent flame retardant properties.

[0004] The present invention provides a low-density and low-thermal-conductivity two-component polyurethane structural adhesive, which is composed of a component A and a component B in a volume ratio of (0.8-1.2):1;

[0005] The A component comprises:

[0006] 10 to 40 parts by weight of modified castor oil;

[0007] 10 to 20 parts by weight of polyether polyol;

[0008] 1 to 5 parts by weight of chain extender;

[0009] 20 to 40 parts by weight of flame retardant filler;

[0010] 1 to 20 parts by weight of hollow filler;

[0011] 1 to 5 parts by weight of white carbon black;

[0012] 1 to 5 parts by weight of molecular sieve;

[0013] 0.1 to 1 parts by weight of tackifier;

[0014] 0.1 to 1 parts by weight of yellow color paste;

[0015] The B component includes:

[0016] 30 to 50 parts by weight of isocyanate;

[0017] 10 to 30 parts by weight of polyester polyol;

[0018] 20 to 40 parts by weight of flame retardant filler;

[0019] 1 to 20 parts by weight of hollow filler;

[0020] 1 to 5 parts by weight of white carbon black;

[0021] 1 to 5 parts by weight of molecular sieve;

[0022] 0.1 to 1 parts by weight of anti-aging agent;

[0023] 0.1 to 1 parts by weight of water absorbent;

[0024] 0.1 to 1 parts by weight of blue color paste.

[0025] Preferably, the modified castor oil is selected from Itoh Oil URIC AC-009 and / or BIOPOL S-3009.

[0026] Preferably, the polyether polyol is selected from HMP-604B and / or HP-2280.

[0027] Preferably, the chain extender is selected from 2-ethyl-1,3-hexanediol and / or trimethylolpropane.

[0028] Preferably, the flame retardant filler is melamine urate; the hollow filler is hollow glass microspheres and / or hollow plastic microspheres.

[0029] Preferably, the tackifier is selected from BYK BYK-4511 and / or ShinEtsu KR-517.

[0030] Preferably, the isocyanate is selected from carbodiimide-uretonimine modified 4,4'-diphenylmethane diisocyanate and / or liquefied 4,4'-diphenylmethane diisocyanate;

[0031] The polyester polyol is an amorphous dimer acid modified polyester polyol.

[0032] The present invention also provides a method for preparing the low-density and low-thermal-conductivity two-component polyurethane structural adhesive described in the above technical solution, comprising the following steps:

[0033] a) heating modified castor oil, polyether polyol, chain extender, flame retardant filler, hollow filler and white carbon black to 110° C. to 130° C., mixing and dehydrating under vacuum, then cooling to below 50° C., adding molecular sieve, tackifier and yellow color paste, and mixing under vacuum to obtain component A;

[0034] b) after the isocyanate and the dehydrated polyester polyol are reacted for the first time, the flame retardant filler, the hollow filler, the white carbon black, the molecular sieve, the anti-aging agent, the water absorbent, and the blue color paste are added to carry out a second reaction to obtain component B;

[0035] c) mixing the above-mentioned component A and component B in a volume ratio of (0.8-1.2):1 to obtain a low-density and low-thermal-conductivity two-component polyurethane structural adhesive;

[0036] There is no restriction on the order of step a) and step b).

[0037] Preferably, the mixing method of heating to 110°C to 130°C in step a) is stirring, and the stirring speed is 400rpm to 600rpm;

[0038] The vacuum degree of the vacuum dehydration is -0.08MPa to -0.1MPa, and the time is 1.5h to 2.5h;

[0039] The vacuum degree of the vacuum mixing is -0.08MPa to -0.1MPa, the rotation speed is 50rpm to 150rpm, and the time is 30min to 60min.

[0040] Preferably, the temperature of the first reaction in step b) is 70°C to 90°C, the speed is 80rpm to 120rpm, the vacuum degree is -0.08MPa to -0.1MPa, and the time is 1.5h to 2.5h;

[0041] The temperature of the second reaction is 10° C. to 40° C., the rotation speed is 180 rpm to 220 rpm, the vacuum degree is -0.08 MPa to -0.1 MPa, and the time is 0.5 h to 1.5 h.

[0042] The invention provides a low-density and low-thermal-conductivity two-component polyurethane structural adhesive, which is composed of a component A and a component B in a volume ratio of (0.8-1.2):1; the component A comprises: 10 to 40 parts by weight of modified castor oil; 10 to 20 parts by weight of polyether polyol; 1 to 5 parts by weight of a chain extender; 20 to 40 parts by weight of a flame retardant filler; 1 to 20 parts by weight of a hollow filler; 1 to 5 parts by weight of white carbon black; 1 to 5 parts by weight of a molecular sieve; 0.1 to 10 parts by weight of a thickener; 1 part by weight to 1 part by weight; 0.1 part by weight to 1 part by weight of yellow color paste; the B component includes: 30 parts by weight to 50 parts by weight of isocyanate; 10 parts by weight to 30 parts by weight of polyester polyol; 20 parts by weight to 40 parts by weight of flame retardant filler; 1 part by weight to 20 parts by weight of hollow filler; 1 part by weight to 5 parts by weight of white carbon black; 1 part by weight to 5 parts by weight of molecular sieve; 0.1 part by weight to 1 part by weight of anti-aging agent; 0.1 part by weight to 1 part by weight of water absorbent; 0.1 part by weight to 1 part by weight of blue color paste. Compared with the prior art, the low-density and low-thermal-conductivity two-component polyurethane structural adhesive provided by the present invention adopts specific components in specific contents to achieve better overall interaction. The product has low density, low thermal conductivity, high bonding strength, and is a non-foaming type with excellent flame retardant structural adhesive, which solves the problems of excessively high density and excessively high thermal conductivity of the current two-component polyurethane structural adhesive.

[0043] In addition, the preparation method provided by the present invention has simple process, mild conditions, easy control, low requirements on equipment, and has broad application prospects. DETAILED DESCRIPTION

[0044] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0045] The present invention provides a low-density and low-thermal-conductivity two-component polyurethane structural adhesive, which is composed of a component A and a component B in a volume ratio of (0.8-1.2):1;

[0046] The A component comprises:

[0047] 10 to 40 parts by weight of modified castor oil;

[0048] 10 to 20 parts by weight of polyether polyol;

[0049] 1 to 5 parts by weight of chain extender;

[0050] 20 to 40 parts by weight of flame retardant filler;

[0051] 1 to 20 parts by weight of hollow filler;

[0052] 1 to 5 parts by weight of white carbon black;

[0053] 1 to 5 parts by weight of molecular sieve;

[0054] 0.1 to 1 parts by weight of tackifier;

[0055] 0.1 to 1 parts by weight of yellow color paste;

[0056] The B component includes:

[0057] 30 to 50 parts by weight of isocyanate;

[0058] 10 to 30 parts by weight of polyester polyol;

[0059] 20 to 40 parts by weight of flame retardant filler;

[0060] 1 to 20 parts by weight of hollow filler;

[0061] 1 to 5 parts by weight of white carbon black;

[0062] 1 to 5 parts by weight of molecular sieve;

[0063] 0.1 to 1 part by weight of an anti-aging agent;

[0064] 0.1 to 1 parts by weight of water absorbent;

[0065] 0.1 to 1 parts by weight of blue color paste.

[0066] The present invention provides a low-density and low-thermal-conductivity two-component polyurethane structural adhesive. The downstream customers currently need a structural adhesive glue with low density, low thermal conductivity, high bonding strength, preferably non-foaming type and excellent flame retardant performance. The existing solutions have various unavoidable shortcomings. Therefore, in order to solve the relevant technical problems, the present invention develops a low-density non-foaming two-component polyurethane structural adhesive.

[0067] First of all, it is clear that thermal conductivity and density are positively correlated, that is, the lower the density, the lower the thermal conductivity. Secondly, let's analyze the reasons for the limitations of thermal conductivity and density. The components of polyurethane glue can be simply divided into two categories, resin and filler. The thermal conductivity of pure resin is about 0.2W / m·k, and the density is 1.0~1.1g / cm 3 Fillers such as calcium carbonate, aluminum hydroxide, and silicon powder have high density and thermal conductivity; and in order to meet the flame retardancy requirements, flame retardant fillers must be added to the system, so the thermal conductivity of previous products cannot be very low. After analyzing the reasons, the present invention adopts the following method to develop a new low-density two-component polyurethane structural adhesive:

[0068] (1) Organic non-metallic flame retardant powder is selected as flame retardant powder. Since inorganic metal has high thermal conductivity and high density, it cannot meet the target requirements of the present invention. Therefore, organic non-metallic nitrogen flame retardant powder, i.e. melamine urate, is selected. It has high flame retardant efficiency and low density and thermal conductivity. (2) Hollow fillers are added to the system to further reduce the density and thermal conductivity of the system. Glass microspheres or plastic microspheres can be selected. However, glass microspheres are hard in texture and not as dense as plastic microspheres, so the amount of addition is limited. They can be used for products with lower density and thermal conductivity. Plastic microspheres have extremely low density and strong toughness, so the amount of addition is higher. They can be used for products with extremely low density and thermal conductivity. (3) After selecting the flame retardant filler and hollow filler, it is necessary to select a suitable resin. Since glass microspheres are hard fillers, the glue is easy to be brittle, so it is necessary to adjust the flexible resin. Plastic microspheres are soft fillers, the glue strength is easy to be insufficient, so it is necessary to adjust the rigid resin.

[0069] In the present invention, the low-density and low-thermal-conductivity two-component polyurethane structural adhesive is composed of component A and component B in a volume ratio of (0.8-1.2):1, preferably 1:1.

[0070] In the present invention, the A component comprises:

[0071] 10 to 40 parts by weight of modified castor oil;

[0072] 10 to 20 parts by weight of polyether polyol;

[0073] 1 to 5 parts by weight of chain extender;

[0074] 20 to 40 parts by weight of flame retardant filler;

[0075] 1 to 20 parts by weight of hollow filler;

[0076] 1 to 5 parts by weight of white carbon black;

[0077] 1 to 5 parts by weight of molecular sieve;

[0078] 0.1 to 1 parts by weight of tackifier;

[0079] 0.1 to 1 parts by weight of yellow color paste;

[0080] It is preferably prepared from the following raw materials:

[0081] 34 to 36 parts by weight of modified castor oil;

[0082] 10 to 20 parts by weight of polyether polyol;

[0083] 4 to 5 parts by weight of chain extender;

[0084] 30 parts by weight of flame retardant filler;

[0085] 2 to 15 parts by weight of hollow filler;

[0086] 2 to 3 parts by weight of white carbon black;

[0087] 3 to 4 parts by weight of molecular sieve;

[0088] 0.4 to 0.6 parts by weight of tackifier;

[0089] 0.4 to 0.6 parts by weight of yellow color paste.

[0090] In the present invention, the modified castor oil is preferably selected from Itoh Oil URIC AC-009 and / or BIOPOL S-3009, more preferably Itoh Oil URIC AC-009 or BIOPOL S-3009; the polyether polyol is preferably selected from HMP-604B and / or HP-2280, more preferably HMP-604B or HP-2280; the chain extender is preferably selected from 2-ethyl-1,3-hexanediol and / or trimethylolpropane, more preferably 2-ethyl-1,3-hexanediol or trimethylolpropane; the flame retardant filler is preferably melamine urate, more preferably one or more of XS-MC-15, XS-MC-50, and HTV-089; the hollow filler is preferably hollow glass microspheres and / or hollow plastic microspheres, more preferably HS28, 32P4000, Nouryon Expancel920DET 40d25, Nouryon The white carbon black is preferably CABOT CAB-O-SIL TS-720 or Evonik AEROSIL R202; the molecular sieve is preferably GJH-03A or GraceSylosiv A300; the tackifier is preferably selected from BYK BYK-4511 and / or ShinEtsu KR-517, more preferably BYKBYK-4511 or ShinEtsu KR-517; the yellow color paste is preferably Bomeishi 085-1I4215.

[0091] In the present invention, the B component comprises:

[0092] 30 to 50 parts by weight of isocyanate;

[0093] 10 to 30 parts by weight of polyester polyol;

[0094] 20 to 40 parts by weight of flame retardant filler;

[0095] 1 to 20 parts by weight of hollow filler;

[0096] 1 to 5 parts by weight of white carbon black;

[0097] 1 to 5 parts by weight of molecular sieve;

[0098] 0.1 to 1 part by weight of an anti-aging agent;

[0099] 0.1 to 1 parts by weight of water absorbent;

[0100] 0.1 to 1 parts by weight of blue color paste;

[0101] It is preferably prepared from the following raw materials:

[0102] 35 to 44 parts by weight of isocyanate;

[0103] 18 to 22 parts by weight of polyester polyol;

[0104] 24 parts by weight of flame retardant filler;

[0105] 2 to 15 parts by weight of hollow filler;

[0106] 2 to 3 parts by weight of white carbon black;

[0107] 3 to 4 parts by weight of molecular sieve;

[0108] 0.9 to 1 part by weight of an anti-aging agent;

[0109] 0.4 to 0.6 parts by weight of water absorbent;

[0110] 0.4 to 0.6 parts by weight of blue color paste.

[0111] In the present invention, the flame retardant filler, hollow filler, white carbon black and molecular sieve are the same as those in the above-mentioned component A, and are not described in detail here.

[0112] In the present invention, the isocyanate is preferably selected from carbodiimide-uretonimine modified 4,4'-diphenylmethane diisocyanate and / or liquefied 4,4'-diphenylmethane diisocyanate, more preferably carbodiimide-uretonimine modified 4,4'-diphenylmethane diisocyanate or liquefied 4,4'-diphenylmethane diisocyanate; the polyester polyol is preferably an amorphous dimer acid modified polyester polyol, more preferably Oleon RADIA 7285 or Cargill Priplast 3187; the anti-aging agent is preferably Chinox TP-10H or BASF Irganox B215; the water absorbent is preferably Borchers TI or LANXESS Trixene ASF; the blue color paste is preferably Bomeishi 085-5M4214.

[0113] The present invention has no special restrictions on the sources of the raw materials in the above-mentioned component A and component B, and commercially available products well known to those skilled in the art can be used.

[0114] The present invention provides a low-density, low-thermal-conductivity two-component polyurethane structural adhesive, which uses specific components at specific contents to achieve better overall interaction: on the one hand, the filler is matched, that is, the combination of melamine urate organic flame retardant powder + hollow filler to reduce the density and thermal conductivity of the system, and at the same time, according to the degree of density reduction, the hollow filler is appropriately selected from hollow glass microspheres or hollow plastic microspheres; on the other hand, the resin formula is matched accordingly, and the hardness of the resin is appropriately changed according to the type of hollow filler to prepare a two-component polyurethane glue with balanced comprehensive performance. Compared with the prior art, the low-density, low-thermal-conductivity two-component polyurethane structural adhesive provided by the present invention can achieve a density range of 0.5 to 1.0 g / cm 3 , thermal conductivity is 0.10~0.25W / m·k, and flame retardant performance is excellent; in terms of mechanical properties, the hardness of the glue is 50~80shore-D, the tensile strength of the body is 8~12MPa, the elongation at break is 20~60%, the bonding strength for 3003AL substrate is 10~15MPa, and the pull-out strength for 3003AL substrate is 12~18MPa; in terms of electrical insulation performance, the volume resistivity of the glue is greater than 1×10^14Ω·cm, and the breakdown voltage is greater than 20kV / mm; in terms of aging performance, after high temperature and high humidity aging, the bonding strength of the glue to the 3003AL substrate is basically not attenuated.

[0115] The present invention also provides a method for preparing the low-density and low-thermal-conductivity two-component polyurethane structural adhesive described in the above technical solution, comprising the following steps:

[0116] a) heating modified castor oil, polyether polyol, chain extender, flame retardant filler, hollow filler and white carbon black to 110° C. to 130° C., mixing and dehydrating under vacuum, then cooling to below 50° C., adding molecular sieve, tackifier and yellow color paste, and mixing under vacuum to obtain component A;

[0117] b) after the isocyanate and the dehydrated polyester polyol are reacted for the first time, the flame retardant filler, the hollow filler, the white carbon black, the molecular sieve, the anti-aging agent, the water absorbent, and the blue color paste are added to carry out a second reaction to obtain component B;

[0118] c) mixing the above-mentioned component A and component B in a volume ratio of (0.8-1.2):1 to obtain a low-density and low-thermal-conductivity two-component polyurethane structural adhesive;

[0119] There is no restriction on the order of step a) and step b).

[0120] In the present invention, the above-mentioned raw materials are the same as those described in the above-mentioned technical solution, and the present invention will not repeat them here.

[0121] In the present invention, the mixing method of heating to 110°C to 130°C in step a) is preferably stirring, and the stirring speed is preferably 400rpm to 600rpm, more preferably 500rpm; the vacuum degree of the vacuum dehydration is preferably -0.08MPa to -0.1MPa, and the time is preferably 1.5h to 2.5h; the vacuum degree of the vacuum mixing is preferably -0.08MPa to -0.1MPa, the rotation speed is preferably 50rpm to 150rpm, more preferably 100rpm, and the time is preferably 30min to 60min.

[0122] In the present invention, the temperature of the first reaction in step b) is preferably 70°C to 90°C, more preferably 80°C, the rotation speed is preferably 80rpm to 120rpm, more preferably 100rpm, the vacuum degree is preferably -0.08MPa to -0.1MPa, and the time is preferably 1.5h to 2.5h; the temperature of the second reaction is preferably 10°C to 40°C, more preferably 20°C to 30°C, the rotation speed is preferably 180rpm to 220rpm, more preferably 200rpm, the vacuum degree is preferably -0.08MPa to -0.1MPa, and the time is preferably 0.5h to 1.5h.

[0123] In the present invention, the dehydration process in step b) is preferably specifically as follows:

[0124] The polyester polyol is vacuumed to -0.08 MPa to -0.1 MPa at 110° C. to 130° C. and dehydrated for 1.5 h to 2.5 h to obtain the dehydrated polyester polyol.

[0125] In the present invention, the drying process in step b) is preferably specifically as follows:

[0126] The flame retardant filler, hollow filler and white carbon black are dried and dehydrated in a drying room at 90° C. to 110° C. for 45 h to 50 h to obtain the dried flame retardant filler, hollow filler and white carbon black.

[0127] The preparation method provided by the invention has simple process, mild conditions, easy control, low requirements on equipment, and has broad application prospects.

[0128] The invention provides a low-density and low-thermal-conductivity two-component polyurethane structural adhesive, which is composed of a component A and a component B in a volume ratio of (0.8-1.2):1; the component A comprises: 10 to 40 parts by weight of modified castor oil; 10 to 20 parts by weight of polyether polyol; 1 to 5 parts by weight of a chain extender; 20 to 40 parts by weight of a flame retardant filler; 1 to 20 parts by weight of a hollow filler; 1 to 5 parts by weight of white carbon black; 1 to 5 parts by weight of a molecular sieve; 0.1 to 10 parts by weight of a thickener; 1 part by weight to 1 part by weight; 0.1 part by weight to 1 part by weight of yellow color paste; the B component includes: 30 parts by weight to 50 parts by weight of isocyanate; 10 parts by weight to 30 parts by weight of polyester polyol; 20 parts by weight to 40 parts by weight of flame retardant filler; 1 part by weight to 20 parts by weight of hollow filler; 1 part by weight to 5 parts by weight of white carbon black; 1 part by weight to 5 parts by weight of molecular sieve; 0.1 part by weight to 1 part by weight of anti-aging agent; 0.1 part by weight to 1 part by weight of water absorbent; 0.1 part by weight to 1 part by weight of blue color paste. Compared with the prior art, the low-density and low-thermal-conductivity two-component polyurethane structural adhesive provided by the present invention adopts specific components in specific contents to achieve better overall interaction. The product has low density, low thermal conductivity, high bonding strength, and is a non-foaming type with excellent flame retardant structural adhesive, which solves the problems of excessively high density and excessively high thermal conductivity of the current two-component polyurethane structural adhesive.

[0129] In addition, the preparation method provided by the present invention has simple process, mild conditions, easy control, low requirements on equipment, and has broad application prospects.

[0130] In order to further illustrate the present invention, the following examples are provided for detailed description. The raw materials involved in the following examples of the present invention are as follows:

[0131] Modified castor oil: Itoh Oil URIC AC-009, Beijing Oil Treasure BIOPOL S-3009;

[0132] Polyether polyol: Royal Madrid HMP-604B, Shanghai Yinman Chemical HP-2280;

[0133] Chain extender: 2-ethyl-1,3-hexanediol (EHD), trimethylolpropane (TMP);

[0134] Flame retardant filler: mainly melamine urate, Xusen XS-MC-15, Xusen XS-MC-50, Jinge HTV-089;

[0135] Flame retardant filler for comparative example: mainly aluminum hydroxide, JAZ-119;

[0136] Hollow fillers: mainly hollow glass microspheres and hollow plastic microspheres, including Sanlight HS28, Sinosteel 32P4000, Nouryon Expancel 920DET 40d25, and Nouryon Expancel920DET 20d40;

[0137] White carbon black: CABOT CAB-O-SIL TS-720, Evonik AEROSIL R202;

[0138] Molecular sieve: Guangji GJH-03A, Grace Sylosiv A300;

[0139] Tackifier: BYK BYK-4511, ShinEtsu KR-517;

[0140] Yellow color paste: Bomax 085-1I4215;

[0141] Isocyanate: Wanhua carbodiimide-uretonimine modified 4,4'-diphenylmethane diisocyanate (CDMDI-100L), Wanhua liquefied 4,4'-diphenylmethane diisocyanate (MDI-50);

[0142] Polyester polyols: mainly amorphous dimer acid modified polyester polyols, Oleon RADIA 7285, CargillPriplast 3187;

[0143] Anti-aging agent: Double Bond Chinox TP-10H from Taiwan, China, BASF Irganox B215;

[0144] Water absorbent: Borchers TI, LANXESS Trixene ASF;

[0145] Blue color paste: Baomeishi 085-5M4214.

[0146] Example 1

[0147] Component A: 35 parts by weight of URIC AC-009 modified castor oil, 15 parts by weight of HMP-604B polyether polyol, 5 parts by weight of EHD chain extender, 30 parts by weight of XS-MC-15 flame retardant filler, 8 parts by weight of HS28 hollow filler, 2 parts by weight of TS-720 white carbon black, 4 parts by weight of GJH-03A molecular sieve, 0.5 parts by weight of BYK-4511 tackifier, and 0.5 parts by weight of yellow color paste.

[0148] Component B: 40 parts by weight of CDMDI-100L isocyanate, 20 parts by weight of RADIA 7285 polyester polyol, 24 parts by weight of XS-MC-15 flame retardant filler, 8 parts by weight of HS28 hollow filler, 2 parts by weight of TS-720 white carbon black, 4 parts by weight of GJH-03A molecular sieve, 1 part by weight of TP-10H anti-aging agent, 0.5 parts by weight of TI water absorbent, and 0.5 parts by weight of blue color paste.

[0149] Example 2

[0150] Component A: 34 parts by weight of URIC AC-009 modified castor oil, 10 parts by weight of HMP-604B polyether polyol, 4 parts by weight of EHD chain extender, 30 parts by weight of XS-MC-15 flame retardant filler, 15 parts by weight of 32P4000 hollow filler, 2 parts by weight of TS-720 white carbon black, 4 parts by weight of GJH-03A molecular sieve, 0.5 parts by weight of BYK-4511 tackifier, and 0.5 parts by weight of yellow color paste.

[0151] Component B: 40 parts by weight of CDMDI-100L isocyanate, 20 parts by weight of RADIA 7285 polyester polyol, 24 parts by weight of XS-MC-15 flame retardant filler, 15 parts by weight of 32P4000 hollow filler, 2 parts by weight of TS-720 white carbon black, 4 parts by weight of GJH-03A molecular sieve, 1 part by weight of TP-10H anti-aging agent, 0.5 parts by weight of TI water absorbent, and 0.5 parts by weight of blue color paste.

[0152] Example 3

[0153] Component A: 36 parts by weight of BIOPOL S-3009 modified castor oil, 20 parts by weight of HP-2280 polyether polyol, 5 parts by weight of TMP chain extender, 30 parts by weight of XS-MC-50 flame retardant filler, 2 parts by weight of Expancel 920DET 40d25 hollow filler, 2 parts by weight of R202 white carbon black, 4 parts by weight of Sylosiv A300 molecular sieve, 0.5 parts by weight of KR-517 tackifier, and 0.5 parts by weight of yellow color paste.

[0154] Component B: 44 parts by weight of MDI-50 isocyanate, 20 parts by weight of Priplast 3187 polyester polyol, 24 parts by weight of XS-MC-50 flame retardant filler, 2 parts by weight of Expancel 920DET 40d25 hollow filler, 2 parts by weight of R202 white carbon black, 4 parts by weight of Sylosiv A300 molecular sieve, 1 part by weight of Irganox B215 antioxidant, 0.5 parts by weight of Trixene ASF water absorbent, and 0.5 parts by weight of blue color paste.

[0155] Example 4

[0156] Component A: 35 parts by weight of BIOPOL S-3009 modified castor oil, 20 parts by weight of HP-2280 polyether polyol, 5 parts by weight of TMP chain extender, 30 parts by weight of HTV-089 flame retardant filler, 3 parts by weight of Expancel 920DET 20d40 hollow filler, 2 parts by weight of R202 white carbon black, 4 parts by weight of Sylosiv A300 molecular sieve, 0.5 parts by weight of KR-517 tackifier, and 0.5 parts by weight of yellow color paste.

[0157] Component B: 44 parts by weight of MDI-50 isocyanate, 21 parts by weight of Priplast 3187 polyester polyol, 24 parts by weight of HTV-089 flame retardant filler, 3 parts by weight of Expancel 920DET 20d40 hollow filler, 2 parts by weight of R202 white carbon black, 4 parts by weight of Sylosiv A300 molecular sieve, 1 part by weight of Irganox B215 antioxidant, 0.5 parts by weight of Trixene ASF water absorbent, and 0.5 parts by weight of blue color paste.

[0158] Comparative Example 1

[0159] Component A: 34 parts by weight of URIC AC-009 modified castor oil, 10 parts by weight of HMP-604B polyether polyol, 4 parts by weight of EHD chain extender, 30 parts by weight of JAZ-119 flame retardant filler, 15 parts by weight of 32P4000 hollow filler, 2 parts by weight of TS-720 white carbon black, 4 parts by weight of GJH-03A molecular sieve, 0.5 parts by weight of BYK-4511 tackifier, and 0.5 parts by weight of yellow color paste.

[0160] Component B: 40 parts by weight of CDMDI-100L isocyanate, 20 parts by weight of RADIA 7285 polyester polyol, 24 parts by weight of JAZ-119 flame retardant filler, 15 parts by weight of 32P4000 hollow filler, 2 parts by weight of TS-720 white carbon black, 4 parts by weight of GJH-03A molecular sieve, 1 part by weight of TP-10H anti-aging agent, 0.5 parts by weight of TI water absorbent, and 0.5 parts by weight of blue color paste.

[0161] Comparative Example 2

[0162] Component A: 38 parts by weight of BIOPOL S-3009 modified castor oil, 20 parts by weight of HP-2280 polyether polyol, 5 parts by weight of TMP chain extender, 30 parts by weight of XS-MC-50 flame retardant filler, 2 parts by weight of R202 white carbon black, 4 parts by weight of Sylosiv A300 molecular sieve, 0.5 parts by weight of KR-517 tackifier, and 0.5 parts by weight of yellow color paste.

[0163] Component B: 46 parts by weight of MDI-50 isocyanate, 22 parts by weight of Priplast 3187 polyester polyol, 24 parts by weight of XS-MC-50 flame retardant filler, 2 parts by weight of R202 white carbon black, 4 parts by weight of Sylosiv A300 molecular sieve, 1 part by weight of Irganox B215 antioxidant, 0.5 parts by weight of Trixene ASF water absorbent, and 0.5 parts by weight of blue color paste.

[0164] The above formula is shown in Table 1 below.

[0165] Table 1

[0166]

[0167]

[0168] The specific preparation methods of the two-component polyurethane structural adhesives provided in the above embodiments and comparative examples are as follows:

[0169] Component A:

[0170] The modified castor oil, polyether polyol, chain extender, flame retardant filler, hollow filler and white carbon black were heated to 120°C with stirring at 500 rpm, evacuated to below -0.09 MPa and dehydrated for 2 hours, then cooled to below 50°C, molecular sieves, tackifiers and yellow color paste were added, evacuated to below -0.09 MPa and stirred at 100 rpm for 45 minutes to obtain component A.

[0171] Component B:

[0172] Firstly, the flame retardant filler, hollow filler and white carbon black are dried and dehydrated in a drying room at 100°C for 48 hours for use;

[0173] The polyester polyol was vacuumed to below -0.09 MPa at 120°C and dehydrated for 2 hours for later use;

[0174] The isocyanate and the dehydrated polyester polyol were stirred at 100 rpm at 80°C and evacuated to -0.09 MPa for 2 hours, and then the flame retardant filler, hollow filler and white carbon black dried in advance were added, and molecular sieves, anti-aging agents, water absorbents and blue color paste were added. The mixture was stirred at 200 rpm at room temperature and evacuated to -0.09 MPa for 1 hour to obtain component B.

[0175] Finally, the above-mentioned component A and component B are evenly mixed in a volume ratio of 1:1 to obtain a low-density and low-thermal-conductivity two-component polyurethane structural adhesive.

[0176] The various properties of the two-component polyurethane structural adhesive provided in each embodiment and comparative example were tested, and the test standards / methods were as follows:

[0177] Density: GB / T 533-2008, Determination of density of vulcanized rubber or thermoplastic rubber;

[0178] Thermal conductivity: ASTM D5470, Standard test method for thermal conductivity of thermally conductive electrical insulating materials;

[0179] Hardness: GB / T 531.1-2008, Standard for the test method of indentation hardness of vulcanized rubber or thermoplastic rubber;

[0180] Bulk tensile strength: GB / T 528-2009, Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber;

[0181] Elongation at break: GB / T 528-2009, Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber;

[0182] Shear strength: GB / T 7124-2008, Determination of tensile shear strength of adhesives (rigid material to rigid material);

[0183] Pull-out strength: GB T 6329-1996, Determination of tensile strength of adhesive butt joints;

[0184] Volume resistivity: ASTM D257, Standard Test Method for DC Resistance or Conductance of Insulating Materials;

[0185] Breakdown voltage: ASTM D149, Test method for dielectric breakdown voltage and dielectric strength of solid electrical insulating materials at industrial power frequencies;

[0186] High temperature and high humidity aging (85℃ / 85% RH): GB / T 2423.50-2012, Environmental testing for electrical and electronic products Part 2: Test method Steady state damp heat is mainly used for accelerated testing of components.

[0187] The test results are shown in Table 2 below.

[0188] Table 2

[0189] Performance Indicators Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Comparative Example 2 <![CDATA[Density (g / cm 3 )]]> 0.95 0.80 0.65 0.55 0.85 1.20 Thermal conductivity (W / m·k) 0.22 0.20 0.17 0.15 0.30 0.33 Hardness (Shore-D) 60 65 58 55 62 62 Main tensile strength (MPa) 10.5 12.0 9.5 9.0 11.5 10.7 Elongation at break (%) 40 20 50 60 40 70 Shear strength(MPa) 12.5 13.0 10.5 10.0 12.7 11.5 Tensile strength (MPa) 14.5 15.0 13.0 12.0 14.4 12.6 Volume resistivity (Ω·cm) 2×10^14 3×10^14 2×10^14 4×10^14 1×10^14 3×10^14 Breakdown voltage(kV / mm) 25.0 27.0 25.0 28.0 23.0 24.0 Shear strength after high temperature and high humidity aging 13.2 13.5 10.7 10.3 12.9 12.2

[0190] The experimental results show that the low-density and low-thermal-conductivity two-component polyurethane structural adhesive provided by the present invention can achieve a reduction in density and thermal conductivity by selecting an organic non-metallic flame-retardant filler + a hollow filler, wherein the hollow glass microspheres are suitable for a density of 0.80 to 1.00 g / cm 3For systems within the range of , if you want to further reduce the density and thermal conductivity of the system, the hollow filler needs to be hollow plastic microspheres; hollow glass microspheres are hard materials, which can easily lead to excessive glue strength and insufficient toughness in the formula, so as much flexible polyol resin as possible needs to be added to the formula, and the rigid resin needs to be appropriately reduced; hollow plastic microspheres are tough materials, which can lead to insufficient glue strength in the formula, so the amount of rigid resin added needs to be appropriately increased in the formula. It can be seen from Comparative Example 1 that if the flame retardant filler is replaced by organic non-metallic melamine urate with inorganic metal aluminum hydroxide, the thermal conductivity of the system will increase significantly; it can be seen from Comparative Example 2 that if no hollow filler is added, the density and thermal conductivity of the system will increase significantly.

[0191] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A low-density, low-thermal-conductivity two-component polyurethane structural adhesive, consisting of component A and component B in a volume ratio of (0.8-1.2):1; The A component includes: 10 to 40 parts by weight of modified castor oil; 10 to 20 parts by weight of polyether polyol; 1 to 5 parts by weight of chain extender; 20 to 40 parts by weight of flame retardant filler; 1 to 20 parts by weight of hollow filler; 1 to 5 parts by weight of white carbon black; 1 to 5 parts by weight of molecular sieve; 0.1 to 1 parts by weight of tackifier; 0.1 to 1 parts by weight of yellow color paste; The B component includes: 30 to 50 parts by weight of isocyanate; 10 to 30 parts by weight of polyester polyol; 20 to 40 parts by weight of flame retardant filler; 1 to 20 parts by weight of hollow filler; 1 to 5 parts by weight of white carbon black; 1 to 5 parts by weight of molecular sieve; 0.1 to 1 parts by weight of anti-aging agent; 0.1 to 1 parts by weight of water absorbent; 0.1 to 1 parts by weight of blue color paste.

2. The low-density and low-thermal-conductivity two-component polyurethane structural adhesive according to claim 1, characterized in that: The modified castor oil is selected from Itoh OilURIC AC-009 and / or BIOPOL S-3009.

3. The low-density and low-thermal-conductivity two-component polyurethane structural adhesive according to claim 1, characterized in that: The polyether polyol is selected from HMP-604B and / or HP-2280.

4. The low-density and low-thermal-conductivity two-component polyurethane structural adhesive according to claim 1, characterized in that: The chain extender is selected from 2-ethyl-1,3-hexanediol and / or trimethylolpropane.

5. The low-density and low-thermal-conductivity two-component polyurethane structural adhesive according to claim 1, characterized in that: The flame retardant filler is melamine urate; the hollow filler is hollow glass microspheres and / or hollow plastic microspheres.

6. The low-density and low-thermal-conductivity two-component polyurethane structural adhesive according to claim 1, characterized in that: The tackifier is selected from BYK BYK-4511 and / or ShinEtsu KR-517.

7. The low-density and low-thermal-conductivity two-component polyurethane structural adhesive according to claim 1, characterized in that: The isocyanate is selected from carbodiimide-uretonimine modified 4,4'-diphenylmethane diisocyanate and / or liquefied 4,4'-diphenylmethane diisocyanate; The polyester polyol is an amorphous dimer acid modified polyester polyol.

8. A method for preparing the low-density and low-thermal-conductivity two-component polyurethane structural adhesive according to any one of claims 1 to 7, comprising the following steps: a) heating modified castor oil, polyether polyol, chain extender, flame retardant filler, hollow filler and white carbon black to 110° C. to 130° C., mixing and dehydrating under vacuum, then cooling to below 50° C., adding molecular sieve, tackifier and yellow color paste, and mixing under vacuum to obtain component A; b) after the isocyanate and the dehydrated polyester polyol are reacted for the first time, the flame retardant filler, the hollow filler, the white carbon black, the molecular sieve, the anti-aging agent, the water absorbent, and the blue color paste are added to carry out a second reaction to obtain component B; c) mixing the above-mentioned component A and component B in a volume ratio of (0.8-1.2):1 to obtain a low-density and low-thermal-conductivity two-component polyurethane structural adhesive; There is no restriction on the order of step a) and step b).

9. The preparation method according to claim 8, characterized in that: The mixing method of heating to 110° C. to 130° C. in step a) is stirring, and the stirring speed is 400 rpm to 600 rpm; The vacuum degree of the vacuum dehydration is -0.08MPa to -0.1MPa, and the time is 1.5h to 2.5h; The vacuum degree of the vacuum mixing is -0.08MPa to -0.1MPa, the rotation speed is 50rpm to 150rpm, and the time is 30min to 60min.

10. The preparation method according to claim 8, characterized in that: The temperature of the first reaction in step b) is 70°C to 90°C, the speed is 80rpm to 120rpm, the vacuum degree is -0.08MPa to -0.1MPa, and the time is 1.5h to 2.5h; The temperature of the second reaction is 10° C. to 40° C., the rotation speed is 180 rpm to 220 rpm, the vacuum degree is -0.08 MPa to -0.1 MPa, and the time is 0.5 h to 1.5 h.

Citation Information

Patent Citations

  • Low-density heat-insulation power battery polyurethane pouring sealant

    CN114621721A

  • Low-density heat-insulating two-component polyurethane structural adhesive for power battery and preparation method of low-density heat-insulating two-component polyurethane structural adhesive

    CN116162435A

  • Low-density two-component polyurethane potting structural adhesive and application thereof

    CN116694295A

  • Low-density two-component polyurethane pouring sealant as well as preparation method and application thereof

    CN117210183A

  • Low-density two-component polyurethane heat-conducting structural adhesive for power battery and preparation method of low-density two-component polyurethane heat-conducting structural adhesive

    CN117363308A